A Contrastive Picture of the Culture of City in Markandaya’s Novels: Examining the Cultural Contrast between City and Country in Markandaya's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Markandaya generally presents a contrastive picture of the culture of the city in that of the country without going to the city, Rukmani and Nathan would not have realized the need for common between the two.